The little walking leaves from Iguazú National Park (Ne Argentina) - Comparisons between subtropical and tropical Typophyllum species (Orthoptera: Tettigoniidae: Pterochrozinae) - Braun, Holger (2015)
In the woods around the famous Iguazú Waterfalls were discovered numerous individuals of a little walking leaf identified as Typophyllum inflatum, a species long ago described from Bolivia, and apparently never reported again. So far this population represents the southernmost known record of katydids comprising the leaf-mimicking family group Pterochrozinae or Pterochrozini. Males of T. inflatum produce a continuous low-ultrasound pure-tone song, which could reveal the presence of this species in other areas with suitable habitat. This song is astonishingly similar to that of T. erosifolium, an allopatric species distributed in northwestern South America. Typophyllum inflatum shares with other Typophyllum species the pre-copulatory riding of the tiny male on the much bigger female, but this occupies only a few hours compared to up to several days in a species from Ecuador. This could be related to a possibly lower predation pressure in the subtropical region. The same may be true of the lower variability of body color, unless this only reflects adaptation to a drier environment. In contrast to tropical species, T. inflatum in northeastern Argentina most likely is seasonal, with adults probably appearing during the south-hemispherical summer.